Long-Term Consequences of Intraoperative Spillage of Bile and Gallstones During Laparoscopic Cholecystectomy (Indian Journal of Forensic Medicine & Toxicology, 2021)
Compared to open cholecystectomy, laparoscopic cholecystectomy is linked to a greater rate of iatrogenic gallbladder perforation. The long-term effects of gallstones and spilled bile are unknown. Over a three-year period, data were gathered prospectively from 1059 patients who had laparoscopic cholecystectomy. The operating techniques and postoperative outcomes of individuals who had gallbladder perforation were examined in detail. Long-term follow-up (varying from 24 to 59 months) was available for 92 % of patients. The gallbladder was perforated in 306 patients (29%); it was more prevalent in men and was linked to increasing age, body weight, and the presence of omental adhesions (all P less than 0.001). Patients with acute cholecystitis had no higher risk (P = 0.13). Pyrexia was more likely postoperatively in individuals who had gallbladder contents spilled (18% vs. 9%; P less than 0.001). Intra-abdominal abscesses formed in 1 (0.6%) of 177 patients with just bile leakage and 3 (2.9 %) of 102 patients with both gallstones and bile spilling, but no intra-abdominal abscesses formed in the 696 patients in whom the gallbladder was removed intact (P less than 0.001). During laparoscopic cholecystectomy, intraperitoneal leakage of gallbladder contents is linked to an increased risk of intra-abdominal abscess. Attempts should be undertaken to irrigate the operating field in order to drain spilt bile and retrieve all gallstones that may have been spilled during the process.
Keywords: Gallbladder, laparoscopic, gallstones, abscesses, cholecystectomy.